ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL SERTA PENGARUHNYA TERHADAP KINERJA MODAL SENDIRI PADA PERUSAHAAN JASA DI BURSA EFEK INDONESIA - DARMAWAN, AMELIA (Kajian Ilmiah Mahasiswa Manajemen, 2013)
This study was made in order to analyze the factors that influence the capital structure and its influence on performance of equiy. There are three control variables used were variable firm size, sales growth, and profitability. Population in this research is service companies in the period 2008-2011 are listed on the Stock Exchange (Indonesia Stock Exchange). The samples in this study using purposive sampling method with secondary data are a source of research data. Then be tested by using multiple regression analysis test methods, the classical assumption, and the goodness of fit test model. Data were processed using eviews 7.0 software. From the test results show that profitability significantly influence capital structure. But sales growth and firm size does not affect the capital structure. As for the performance of the equity, sales growth has a significant impact on equities performance. On the contrary the company size and profitability are not significantly influence the performance of the equity.